2005
DOI: 10.1007/s11172-006-0075-8
|View full text |Cite
|
Sign up to set email alerts
|

Volume parameters of some Diels-Alder reactions involving C=C, C=S, and N=N bonds

Abstract: The effect of a hydrostatic pressure of up to 1000 kg cm -2 on the rate constants of the Diels-Alder reactions of maleic anhydride with 1,2,3,4 tetraphenylcyclopentadiene and with 6,13 dichloropentacene, of 4 phenyl 1,2,4 triazoline 3,5 dione with hexachlorocyclo pentadiene, and of thiobenzophenone with isoprene was studied at 25 °С. The volume param eters and ratios of the activation to reaction volumes make it possible to exclude electrostriction of the solvent during transition state solvation in all the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…15 In a recent study, the volume parameters of the reaction of thiobenzophenone with isoprene were determined, and on this basis the authors concluded that a concerted reaction mechanism is followed. 16 In recent reports, asymmetric thia-Diels-Alder reactions of activated dithioesters 17 as well as of aryl-and hetaryl thioketones 18 with an in-situ-generated chiral trienamine were presented. In the second case, a stepwise reaction mechanism via diradical intermediates was proposed.…”
mentioning
confidence: 99%
“…15 In a recent study, the volume parameters of the reaction of thiobenzophenone with isoprene were determined, and on this basis the authors concluded that a concerted reaction mechanism is followed. 16 In recent reports, asymmetric thia-Diels-Alder reactions of activated dithioesters 17 as well as of aryl-and hetaryl thioketones 18 with an in-situ-generated chiral trienamine were presented. In the second case, a stepwise reaction mechanism via diradical intermediates was proposed.…”
mentioning
confidence: 99%
“…It has been well documented [1] that sodium ferrate, Na 2 FeO 4 , is a strong and environmental friendly oxidant. Under the acidic conditions, the redox potential of ferrate (VI) ions is as high as 2.2V.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the product of ferrate oxidation reaction is considered to be ferric hydroxide, which is useful coagulant and will enhance the water remediation performance. Up to now, there are three methods have been reported to synthesis of ferrate: (1) the electrochemical method by which anodic oxidation uses iron or alloy as the anode and NaOH/KOH as the electrolyte. The production yield is revealed to be strongly dependent on the electrolyte temperature and current density; (2) the dry method by which various iron oxide-containing minerals are heated or melted under strong alkaline conditions and with oxygen flow.…”
Section: Introductionmentioning
confidence: 99%